Infant Neurobehavioral Dysregulation Related to Behavior Problems in Children with Prenatal Substance Exposure - Lester, Barry M. (2009)
OBJECTIVE: To test a developmental model of neurobehavioral dysregulation relating prenatal substance exposure to behavior problems at age 7. PATIENTS AND METHODS: The sample included 360 cocaine-exposed and 480 unexposed children from lower to lower middle class families of which 78% were African American. Structural equation modeling (SEM) was used to test models whereby prenatal exposure to cocaine and other substances would result in neurobehavioral dysregulation in infancy, which would predict externalizing and internalizing behavior problems in early childhood. SEM models were developed for individual and combined parent and teacher report for externalizing, internalizing, and total problem scores on the Child Behavior Checklist. RESULTS: The Goodness of Fit Statistics indicated that all of the models met criteria for adequate fit with 7 of the 9 models explaining 18 to 60% of the variance in behavior problems at age 7. The paths in the models indicate that there are direct effects of prenatal substance exposure on 7-year behavior problems as well as indirect effects, including neurobehavioral dysregulation. CONCLUSIONS: Prenatal substance exposure affects behavior problems at age 7 through two mechanisms. The direct pathway is consistent with a teratogenic effect. Indirect pathways suggest cascading effects where prenatal substance exposure results in neurobehavioral dysregulation manifesting as deviations in later behavioral expression. Developmental models provide an understanding of pathways that describe how prenatal substance exposure affects child outcome and have significant implications for early identification and prevention.